Liofilização de pedúnculos de caju (Anacardium occidentale L.) in natura e desidratado osmoticamente - Bastos, Valdeci Silva (2011)
The objective was to evaluate the lyophilization of fresh and osmotically dehydrated cashew (Anacardium ocidentale, L.) and the physical-chemical, microbiological and sensory quality of final product. The osmotic process was carried out by slices 1 cm thickness, 20°C, solution concentration of 30 °Brix, agitation and process time set at 200 min, all defined by preview experiments. Set conditions of osmotic pretreatment cashew slices were frozen in freezer and conventional freeze-drying process was conducted for 25 hours for the fruit with and without osmotic pretreatment. It was obtained the kinetic freezing and freeze-drying kinetics of samples with and without osmotic pretreatment. The influence of process on final product quality was evaluated based on physical and chemical analysis of three different cashew batches for the lyophilized with or not osmotic dehydratation, for vitamin C dry basis levels (80,3 to 90,14 and 90,33 mg/100g to 110,8 mg/100g), carotenoids (0,28 to 0,34 mg/100g and 0,23 to 0,26 mg/100g); tannins (0,06 to 0,1 and 0,05 g/100g to 0,1 g/100g) ashes (0,14 to 0,17 and 0,21 g/100g to 0,3 g/100g), titratable acidity expressed as malic acid (0,06 to 0,16 and 0,18 g/100g to 0,28 g/100g), water activity (0,197 to 0,218 and 0,230 to 0,290), moisture (3,79 to 4,32% and 3,28 to 3,55% wet basis). The parameter color does not change significantly in any of the samples. Lyophilized samples with or without treatment showed shrinkage of up to 18,29% and 8,79% respectively. The products obtained were stable microbiological quality. The lyophilized samples showed no significant difference between them in relation to the aroma and flavor, however the sample lyophilized with osmotic pretreatment showed the highest average for the two attributes evaluated when compared with lyophilized sample without any pretreatment.